INFLUENCE OF CORUNDUM AS COARSE AGGREGATE IN HIGH-PERFORMANCE CONCRETE ON PROJECTILE IMPACT RESISTANCE - Michal Mára; Zdeňka Říhová; Markéta Kočová (Acta Polytechnica CTU Proceedings, 2019)
The aim of this paper is focused on the influence of corundum as coarse aggregate in high-performance concrete on projectile impact resistance in terms of depth of penetration and size of the crater. Based on the experimental programme, samples of high-performance steel-fibre-reinforced concrete with different types and quantities of coarse aggregates were designed and produced, to be subjected to impact loading in the form of projectile impact. Damaged samples were scanned using a 3D scanner and their surface was evaluated. The goal of the paper was to find the optimum content of coarse aggregate in the mixture in order to improve its resistance against projectile impact.